The birth of a network - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
'If we aim for the moon, we might end up on one of those stars' is a heady enough slogan, but quaintly matter-of-fact at the same time. It was often used during a momentous week of networking by a couple of dozen rural women in Madrid, Spain, early...